Creative orientation of formation of musical-aesthetic orientations of the future teachers in cognitive activity (Pedagogy of Higher and Secondary Education, 2006)
The article deals with some problems of aestenc and musical orientations in the process of students' creative activity.
Keywords: creative activity; outside of educational preparation; integration of arts